PENGARUH PERENCANAAN SDM, PELATIHAN, DAN PENGEMBANGAN TERHADAP KINERJA ORGANISASI PEMERINTAHAN KABUPATEN MAROS - Muslimin, Muslimin; Mahfudnurnajamuddin, Mahfudnurnajamuddin; Serlin, Serlin (JURNAL ILMIAH EDUNOMIKA, 2024)
This research is intended to look at the Human Resources (HR) that organize, prepare and improve hierarchical implementation in public authority services in Maros Regency. This study examined the variables that influence HRM organizing, preparing and improving in Maros District services. The review population, consisting of workers in the HR divisions of 23 Maros County services, consisted of 166 respondents. To accomplish the review target, specialists made and conveyed surveys, and gathered and deciphered information utilizing SPSS. General investigations were conducted utilizing expressive measurements and connection examination. The outcomes showed that the arrangement, preparing, and overall improvement of HR were related to authoritative exhibitions in Makassar City Services. This paper provides suggestions for further developing HR in Maros District Services.